Frequency of Depression in Pregnant Patients Presenting to Antenatal Clinic. A Cross-Sectional Study - Sadia Abdul Jabbar, Ayesha Siddiqa Butt, Amjad Hussain Balouch, Waleed Akhtar, Zuhaib Muhammad Ali, Mamona Abdul Jabbar (Pakistan Journal of Medical & Health Sciences, 2023)
Depression is one of the most common complications in pregnancy. Pregnancy, however, makes women more vulnerable to psychological and emotional issues like anxiety, depression, stress & psychoses, which can have a negative impact on the mother and the foetus. Depression is one of the most common complications in pregnancy. Objective: To determine the frequency of depression in pregnant patients presenting to antenatal clinic in Jinnah Hospital, Lahore. Study Design: A Cross-sectional study. Setting: Department of Obstetrics & Gynaecology, Jinnah Hospital, Lahore. Methodology: Total 250 females meeting the inclusion criteria were selected from the OPD. Then patients were assessed by using BDI scoring system by researcher herself. If BDI score was ≥11, then depression during pregnancy was labeled (as per operational definition). All this information was recorded through proforma (attached). Results: The mean age of the women was 32.37±8.10 years. There were 109(43.6%) women with less than equal to 20 weeks of gestational age and 141(56.4%) were having gestational age more than 20 weeks. The mean BDI score was 10.42±9.24. There were 45 (18%) women with depression and 205(82%) women were having no depression. Conclusion: In this study frequency of depression among pregnant women was 18%. However there was no significant association between depression and age, gestational age, parity, BMI and education status of women. Keywords: Depression, Pregnant women, Antenatal clinic.